Penilaian Risiko Kesehatan Lingkungan di Dusun Kokoa Desa Marannu Kecamatan Lau Kabupaten Maros Tahun 2015 - Jumadil Azhar; Andi Susilawaty; Muhammad Saleh (Public Health Department, Universitas Islam Negeri Alauddin Makassar, 2016)
Environmental Health Risk Assessment (EHRA) is a Study to learn condition of sanitation facility and Risk behavior to society health. This Study aims to get description of Environmental Health Risk at Kokoa Hamlet, Marannu Village, District Lau, Maros Regency. Type of study that used is descriptive. Respondents in this study is all of household at Kokoa Hamlet, Marannu Village, District Lau, Maros Regency as much as 72 Households that taken with total sampling method. The result of research is obtainable that environmental health hazard at Kokoa Hamlet, Marannu Village, District Lau covers the hazard of clean water (42,7%), domestic waste water (93,8%) and trash can ownership (90,2%). As for some of unhealthy behavior who gives exposures hazard chance is washing hand without soap (44,4%), defecation anywhere (88,7%), no sorting and processing household rubbish (91,7) along behavior is not treating mineral water (30,6%). It can be concluded that environmental health risk rate at Kokoa Hamlet, Marannu Village, District Lau, Maros Regency that shows very high risk category can be found at 01 Neighbourhood Head, high risk category can be found at 03 Neighbourhood Head, and low risk category can be found at 02 Neighbourhood Head. In this case, risk communication is required so that the society know and understand Environmental Health Risk volume where they live so prevention in the form household scope and individual enhancement can behave clean and healthy.Key words : Risk, Environmental Health, Village